The intervention of the judge regarding expert evidence. Comparison between the United States and Chile’s civil system - Espinoza Diban, Paulina (Revista de Derecho Privado: Debates y tendencias, 2025)
Judges know the law, but they cannot possess expertise in every field. Therefore, in certain cases that require specialized knowledge beyond legal training, reliance on an expert becomes essential to ensure a well-reasoned judgment. This article examines the approach of the United States judicial system toward expert evidence, focusing on the application of the Daubert doctrine and the role of the judge in determining the admissibility of such evidence. The analysis then turns to the continental system —specifically the Chilean model— highlighting how the judge’s intervention occurs primarily at a later stage, during the assessment of expert evidence. Finally, it is shown how these Daubert criteria could be applied by Chilean judges, leading to a convergence between the two systems.